2021
DOI: 10.1029/2021sw002798
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Assessment of the SET HASDM Database

Abstract: covering almost two solar cycles. 11• HASDM models the movement of lighter species during solar minimum condi-12 tions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 52 publications
3
38
0
Order By: Relevance
“…Our results show that 1) JB2008 and HASDM densities agree moderately well with observations during pre-storm periods; 2) JB2008 underestimates and HASDM overestimates densities during storm main phase, and 3) HASDM estimates agree remarkably well with observations during storm recovery, reproducing cooling effects quite well, but JB2008 density levels always surpass observations during the recovery phase. Licata et al (2021b) noted similar trends when comparing CHAMP and GRACE observations with HASDM and JB2008 results for the Halloween storms. Panel e shows the relative errors of the model estimates with respect to observations.…”
Section: Comparing Model Performance During the Extreme Events Observed By Champ And Gracesupporting
confidence: 56%
See 1 more Smart Citation
“…Our results show that 1) JB2008 and HASDM densities agree moderately well with observations during pre-storm periods; 2) JB2008 underestimates and HASDM overestimates densities during storm main phase, and 3) HASDM estimates agree remarkably well with observations during storm recovery, reproducing cooling effects quite well, but JB2008 density levels always surpass observations during the recovery phase. Licata et al (2021b) noted similar trends when comparing CHAMP and GRACE observations with HASDM and JB2008 results for the Halloween storms. Panel e shows the relative errors of the model estimates with respect to observations.…”
Section: Comparing Model Performance During the Extreme Events Observed By Champ And Gracesupporting
confidence: 56%
“…Typically, 75 calibration satellites are used to fit and correct the JB2008 density and the greater the number of calibration satellites, the higher the accuracy. Because HASDM is able to mitigate uncertainty in atmospheric effects, by resolving the differences between calibration satellites and the core JB2008 model at each epoch (time step), real-time nowcasting specification of the LEO drag environment has improved significantly (e.g., Storz et al, 2005;Bowman et al, 2008;Licata et al, 2021b;Calabia and Jin, 2021).…”
Section: Modelsmentioning
confidence: 99%
“…Our results show that (i) JB2008 and HASDM densities agree moderately well with observations during pre-storm periods; (ii) JB2008 underestimates and HASDM overestimates densities during storm main phase, and (iii) HASDM estimates agree remarkably well with observations during storm recovery, reproducing cooling effects quite well, but JB2008 density levels always surpass observations during the recovery phase. Licata et al (2021b) noted similar trends when comparing CHAMP and GRACE observations with HASDM and JB2008 results for the Halloween storms. Panel e shows the relative errors of the model estimates with respect to observations.…”
Section: Comparing Model Performance During the Extreme Events Observ...supporting
confidence: 56%
“…Typically, 75 calibration satellites are used to fit and correct the JB2008 density and the greater the number of calibration satellites, the higher the accuracy. Because HASDM is able to mitigate uncertainty in atmospheric effects, by resolving the differences between calibration satellites and the core JB2008 model at each epoch (time step), real-time nowcasting specification of the LEO drag environment has improved significantly (e.g., Storz et al, 2005;Bowman et al, 2008;Licata et al, 2021b;Calabia and Jin, 2021).…”
Section: Modelsmentioning
confidence: 99%
“…Oftentimes the integrated densities from HASDM are slightly greater than those from EXTEMPLAR. In a comparison between the SET HASDM data set with the JB2008 model and CHAMP and GRACE density measurements, Licata et al (2021) had found that the HASDM density values were also consistently greater than the values derived from the CHAMP and GRACE accelerometer measurements, while matching better than the JB2008 model. Licata et al (2021) also found that during the major storm in October 2003 (the same event shown here in the first half of Figure 6), while the HASDM data set had slightly larger densities than measured with CHAMP GRACE, it did very well at matching the relative changes in density during this period.…”
Section: Discussionmentioning
confidence: 96%